Environmental health : from global to local - Frumkin, Howard (San Francisco, CA : Jossey-Bass, 2010)
From the Publisher: The second edition of Environmental Health: Fr om Global to Local, a comprehensive introductory text, offers an overvi ew of the methodology and paradigms of this burgeoning field, ranging f rom ecology to epidemiology, from toxicology to environmental psycholog y, and from genetics to ethics. Expert contributors discuss the major i ssues in contemporary environmental health: air, water, food safety, o ccupational health, radiation, chemical and physical hazards, vector co ntrol, and injuries. Also emphasizing a wide variety of issues of globa l interest, the thoroughly revised second edition contains updated info rmation on such timely topics as toxicology, exposure assessment, clima te change, population pressure, developing nations and urbanization, en ergy production, building and community design, solid and hazardous was te, and disaster preparedness. In addition, each chapter of Environment al Health includes learning objectives, key points, and discussion ques tions.
Tables, figures, and exhibits -- Editor -- Contributors -- Acknowled gments -- Introduction / Howard Frumkin -- Part 1: Methods And Paradig ms -- 1: Ecology and environmental health / Bruce Wilcox and Holly Jes sop -- 2: Toxicology / Jason R Richardson and Gary W Miller -- 3: Env ironmental and occupational epidemiology / Kyle Steenland and Christine Moe -- 4: Exposure assessment, industrial hygiene, and environmental management / P Barry Ryan -- 5: Environmental psychology / Daniel Stok ols and Chip Clitheroe -- 6: Genetics and environmental health / Samue l H Wilson and William A Suk -- 7: Environmental health ethics / Andre w Jameton -- 8: Environmental justice / Charles Lee -- Part 2: Enviro nmental Health On The Global Scale -- 9: Population pressure / Don Hin richsen -- 10: Climate change / Jonathan A Patz -- 11: Developing nat ions / Jerome Nriagu, Jaymie Meliker, and Markey Johnson -- Part 3: En vironmental Health On The Regional Scale -- 12: Air pollution / Michel le L Bell and Jonathan M Samet -- 13: Energy production / Jeremy J Hes s -- 14: Healthy communities / Sarah K Heaton, John M Balbus, James W Keck, and Andrew L Dannenberg -- 15: Water and health / Tim Ford -- Pa rt 4: Environmental Health On The Local Scale -- 16: Solid and hazard ous waste / Sven Rodenbeck, Kenneth Orloff, and Henry Falk -- 17: Pest control and pesticides / Mark G Robson, George C Hamilton, and Wattasi t Siriwong -- 18: Food safety / David McSwane -- 19: Healthy building s / Howard Frumkin -- 20: Workplace health and safety / Melissa Perry and Howard Hu -- 21: Radiation / Arthur C Upton -- 22: Injuries / Jer emy J Hess and Junaid A Razzak -- 23: Environmental disasters / Mark E Keim -- 24: Nature contact / Howard Frumkin -- 25: Children / Maida P Galvez, Joel Forman, and Philip J Landrigan -- Part 5: Practice Of E nvironmental Health -- 26: Prevention in environmental health / Lynn R Goldman -- 27: Environmental health practice / Sarah Kotchian and Rob ert J Laumbach -- 28: Geographic information systems / Lance A Waller -- 29: Risk assessment / Scott Bartell -- 30: Environmental health po licy / A Stanley Meiburg -- 31: Risk communication / Vincent T Covello -- 32: Legal remedies / Douglas A Henderson -- Index.
Includes bibliographical references and index.
Keywords: Environmental health; Health risk assessment; Environmental Health; Environmental exposure -- Prevention & control; Environmental Medicine -- methods